Negative Impact of Chemotherapy on Breast Cancer Patients QOL - Utility of Antiemetic Treatment Guidelines and the Role of Race - Hassan, Bassam Abdul Rasool; Yusoff, Z. M. (West Asia Organization for Cancer Prevention, 2010)
Introduction: Chemotherapy-induced nausea and vomiting (CINV) is one of the most important worries of cancer patients. Although not life-threatening, it has a great negative impact on quality of life (QOL). Objective: The aim of this study was to determine the impact of CINV (i.e., acute and delayed) on breast cancer patients QOL and to discern opinions related with antiemetic guidelines used dependent on the three main races in Malaysia (Malay, Chinese, Indian). Methods: In this longitudinal prospective observational study, 158 breast cancer patients treated with chemotherapy were interviewed and valid questionnaires (MANE and ONEM) were used to report the impact of CINV on their QOL within the first 24 hours and after 3 to 5 days of chemotherapy treatment. Results: The main result was that delayed CINV has an impact on QOL greater than acute CINV. The impact of nausea was reportedly higher than that of vomiting. Also differences in race i.e., genetic polymorphisms (pharmacogenomics) influenced the utility of antiemetic treatments and patients opinions. Conclusion: Based on the results of our study a new guideline for antiemetic treatment should be used to reduce the impact of CINV on QOL, taking into account variation in genetic polymorphisms among the three races in Malaysia.